A voz e seus en-cantamentos: o fenômeno sonoro na constituição do self e no desenvolvimento humano - Socha, Alexandre (2010)
This theoretical essay proposes an investigation of the human voice and speech, based on its melodic sound and prosody. At first, their historical and cultural aspects will be raised, to then walk towards psychoanalysis and the place which vocal phenomenon occupies in clinical practice. The recognition of sonority and vocal gesture in primary relationships and in the constitution of the self crosses through several issues approached in this research. During this course, an emphasis will be given to communication between mother and baby, particularly seized by the concept of "maternal speech . Underscoring its importance in human development, this study also seeks to think about possible clinical consequences of such understanding of sonority and vocal phenomenon. As much as reference and theoretical support, the work of D.W. Winnicott will be assumed as a central axis, from which dialogues with other authors who have dedicated themselves to the theme will be made